Revisiting Postbariatric Monsplasty - Flavio Henrique Mendes; Fausto Viterbo; José Marcos Gabas; Rafael José de Castro (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: The treatment of the pubic region is an integral part of lower body readjustment in post-bariatric patients, considering the pathophysiology and generalized characteristics of contour deformities after a considerable weight loss. The objective is to present our experience in the treatment of post-bariatric patients, exclusively by low marking of abdominoplasty with appropriate tissue mobilization vectors, without the necessity to leave vertical or oblique scars in the pubic region. METHODS: The medical and photographic records of patients subjected to different abdominal approaches were retrospectively evaluated, applying the principles described above in the combined treatment of the pubic region. A low anterior skin incision was created, and angled cranial detachment towards the aponeurotic plane (with the bevel preserving the deep upper fat) and maintenance of excess fat on the upper edges to facilitate the fixation of the flaps through the superficial fascial system were performed. The outcomes' quality was subjectively evaluated by a single observer. RESULTS: In the case series of 126 consecutive patients, the strategy used restored the best position, tone, and shape of the pubis in 100% of the cases; the results were subjectively classified as good (40%) or very good (60%). The complications more frequently found in the post-operative period were small suture dehiscence (23.8%) and seroma formation (19%), with good evolution provided by dressings and serial punctures. CONCLUSION: The surgical strategy presented involving low positioning of the anterior incision and flap alignment in the superficial fascial system and skin by fixation allows the proper treatment of the pubic region during post-bariatric abdominoplasty procedures, without the need for additional resections and scars.